Towards device technologies non-invasive to our daily lives - Hyeokjun Yoon; Canan Dagdeviren (Nature Communications)
Recent advances in non-invasive technologies have shown disruptive potential for biomedical applications. However, while surgically non-invasive, they may introduce other types of limitations which interfere with the patient’s quality of life, from impracticalities and discomfort in daily life to social stigma.